Distinct binding modes and structural changes induced by cAMP and cGMP in the GAF domain of Anabaena adenylyl cyclase, CyaB2 - Biswas,Kabir H; Badireddy,Suguna; Anand,Ganesh S; Visweswariah,Sandhya S (PeerJ PrePrints, 2014)
GAF domains are a large family of regulatory domains, and a subset are found associated with enzymes involved in cyclic nucleotide (cNMP) metabolism such as adenylyl cyclases and phosphodiesterases. CyaB2, an adenylyl cyclase from Anabaena, contains two GAF domains in tandem at the N-terminus and an adenylyl cyclase domain at the C-terminus. Cyclic AMP, but not cGMP, binding to the GAF domains of CyaB2 increases the activity of the cyclase domain leading to enhanced synthesis of cAMP. Here we show that the isolated GAFb domain of CyaB2 can bind both cAMP and cGMP, and enhanced specificity for cAMP is observed only when both the GAFa and the GAFb domains are present in tandem (GAFab domain). In silico docking and mutational analysis indicated distinct modes of binding of cAMP and cGMP to the GAFb domain. Structural changes associated with ligand binding to the GAF domains could not be detected by the highly sensitive Bioluminescence Resonance Energy Transfer (BRET) experiments. Amide hydrogen-deuterium exchange mass spectrometry (HDXMS) experiments, however, revealed the structural basis for cAMP-induced allosteric regulation of the GAF domains, and differences in the structural changes induced by cAMP and cGMP binding to the GAF domain. Thus, our results provide an insight into structural mechanisms of ligand binding to GAF domains in general, which can be utilized in developing molecules that modulate the allosteric regulation by GAF domains in pharmacologically relevant proteins.
Keywords: BRET; cAMP; cGMP; GAF; cyclases; HDXMS; ligand; phosphodiesterases; structural changes